2020
DOI: 10.1002/phar.2381
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxicity Risk and Clinical Effectiveness of Continuous versus Intermittent Infusion Vancomycin Among Patients in an Outpatient Parenteral Antimicrobial Therapy Program

Abstract: Study Objective To compare rates of nephrotoxicity, time to nephrotoxicity onset, and clinical failure among patients who received continuous infusion (C‐I) or intermittent infusion (I‐I) vancomycin in an outpatient parenteral antimicrobial therapy (OPAT) program. Nephrotoxicity was defined as an increase in serum creatinine greater than 0.5 mg/dl or a 50% increase from baseline for two consecutive measurements while receiving vancomycin during OPAT. Clinical failure was defined as unplanned readmission, exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…With AUC-based vancomycin dosing in OPAT, AKI occurred in 8 of 115 patients (7%) with no AKI-associated readmissions or emergency department visits over 2 years; only 1 patient required a change to an alternate agent due to AKI. Our nephrotoxicity findings are similar to those in recent cohorts using continuous infusion vancomycin as a renal-sparing OPAT strategy, and 1 smaller AUC-directed dosing evaluation [ 5 , 8 ]. Calculating vancomycin AUCs and documenting vancomycin dose adjustments currently represents a substantial portion of our OPAT team's pharmacist workload; this study suggests that streamlined patient care workflow with selective calculation of AUCs could dispense with much of that workload, freeing up pharmacist time for more consistent documentation and other more value-added OPAT activities.…”
Section: Discussionsupporting
confidence: 88%
“…With AUC-based vancomycin dosing in OPAT, AKI occurred in 8 of 115 patients (7%) with no AKI-associated readmissions or emergency department visits over 2 years; only 1 patient required a change to an alternate agent due to AKI. Our nephrotoxicity findings are similar to those in recent cohorts using continuous infusion vancomycin as a renal-sparing OPAT strategy, and 1 smaller AUC-directed dosing evaluation [ 5 , 8 ]. Calculating vancomycin AUCs and documenting vancomycin dose adjustments currently represents a substantial portion of our OPAT team's pharmacist workload; this study suggests that streamlined patient care workflow with selective calculation of AUCs could dispense with much of that workload, freeing up pharmacist time for more consistent documentation and other more value-added OPAT activities.…”
Section: Discussionsupporting
confidence: 88%
“…Vancomycin is an antibiotic used for empiric coverage of methicillinresistant Staphylococcus aureus. Standard methods for administering vancomycin are continuous infusion or intermittent infusion; although these methods do not show significant differences in mortality, 1,2 studies have continued to report that the intermittent infusion of vancomycin (IIV) has a greater risk of developing nephrotoxicity than the continuous infusion of vancomycin (CIV) [3][4][5] A high peak and/or trough serum concentration (>20 mg/L or area under the curve [AUC] for 24 h (AUC 24 ): >700 mg•h/L) of vancomycin is related to nephrotoxicity; [6][7][8] accordingly, a recent study showed that CIV was associated with a 53% reduction in the odds of acute kidney injury compared with IIV, 2 which is most likely because CIV does not cause an excessive rise in the concentration outside the therapeutic range (20-30 mg/L). Despite its merits on concentration control, CIV has the disadvantage of requiring a long time to reach the therapeutic range without a loading dose.…”
Section: Introductionmentioning
confidence: 99%
“…If a CI vancomycin dosing scheme is employed, for example, blood samples can be drawn at any time after steady state has been achieved, and AUC24 can be estimated based on one level. Implementation of CI vancomycin can lead to reduction of 1) amount of care coordination required between OPAT programs, nursing facilities, and home infusion companies; 2) risk of inappropriately timed laboratory testing and delays in antibiotic dose adjustments; and 3) risk of antibiotic-related adverse events [ 30 , 42 ].…”
Section: Safety Monitoringmentioning
confidence: 99%
“…One study found that patients whose OPAT regimen was dosed once or twice daily were more likely to be adherent compared with patients whose antimicrobials were dosed more than twice daily [27••]. To facilitate less frequent dosing and to maximize chances of PK/PD target attainment, certain beta-lactams and vancomycin can be given as a continuous infusion (CI) [28][29][30]. The option for bolus or CI should be explored in advance as some patients may prefer multiple daily dosing, or insurance may not cover the necessary CI infusion pump devices [28].…”
Section: Patient Adherence and Ease Of Antimicrobial Administrationmentioning
confidence: 99%